Evaluation of the difference in clinical manifestations of chronic obstructive pulmonary disease between men and women: an analytical cross-sectional study - Barcelos, Giovanna Guilherme; Carvalho, Isabella Ribeiro de Sena; Araújo, Mariana Alves Santana de; Ferreira, Anna Carolina Galvão; Rabahi, Marcelo Fouad (Revista de Medicina, 2022)
Introduction: Despite being a typically male disease, the prevalence of COPD in women has been rising. Therefore, it’s very important to know its clinical presentation among groups, so the correct clinical approach can be planned. Objectives: Evaluate the difference in COPD symptoms, as well as its impact and the associated risk factors, between men and women. Methodology: Analytical, observational and cross-sectional study where 203 COPD patients were evaluated. Spirometric diagnosis was the most relevant inclusion criteria. A descriptive analysis was stratified between gender and non parametric tests were realized. COPD Assessment Test (CAT), Charlson Comorbidity Index and FRAIL-BR were applied and used to compare genders. Results: The impact of symptoms using the COPD Assessment Test (CAT) was higher in women (p=0,04) and clinically significant. Conclusion: Women with COPD are more symptomatic.